(ØÙƒÙ… Ù…Ø§Ù„ ÙÙŠØ³ÙˆÙƒÙ‰ ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„Ø²ÙˆØ§Ø¬ Ø§Ù„Ø¹Ø±ÙÙŠ (Ø¯Ø±Ø§Ø³Ø© Ù…ÙŠØ¯Ø§Ù†ÙŠØ©ØŒ Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø£Ø±Ø§Ø¡ Ø¹Ø¸Ù…Ø§Ø¡ Ø§Ù„Ø¹Ø§Ø¯Ø© ÙˆØ¹Ù„Ù…Ø§Ø¡ Ø³Ø§Ø³Ø§Ùƒ ÙÙŠ Ù‚Ø±ÙŠØ© Ø£ÙŠÙƒ Ø¯Ø§Ø±ÙŠÙƒ Ù„ÙˆÙ…Ø¨ÙˆÙƒ Ø§Ù„ÙˆØ³Ø·Ù‰ Ù†ÙˆØ³Ø§ ØªÙ†Ø¬Ø±Ø§ Ø§Ù„ØºØ±Ø¨ÙŠØ© - Banani, Naoval; Wahab, Abdul; Masduqi, Ahmad (Maqasid: Jurnal Studi Hukum Islam, 2020)
ABSTRACTThis research was a study of a custom named Pisuke property located on the island of Lombok, the custom is about customary marriage process, and the Pisuke is a gift from the bridegroom in the form of a number of property such as money, rice fields, or animals for the guardian of the bride so that the custom could accept the marriage, it was a gratitude to the bride's guardian who has been taking care and giving her daughter a living since childhood, even though it forces the bridegroom.So, the researcher examined the views of traditional leaders and sasak religious leader in Aiq Darek about the custom, and the purpose of this study are: first, to find out their views, second, to find out the comparison between their views about the Pisuke property law.The method used by the author in this study was a qualitative or empirical method with the data collection techniques such as observation, interview, and documentation, then analyzed it to get conclusions.The conclusions of this study: first, the opinion between the traditional leaders and religious leader of Sasak in Aiq Darek about the Pisuke custom was vary on customary law. secondly, from the their opinion comparison, the custom contained elements of benefit and disadvantage, and the custom must be in line with the Shari'a.Â Keywords: Pisuke Property, Custom, Marriage